ANDROID-BASED MATHEMATICAL LEARNING MEDIA: ONLINE LEARNING ALTERNATIVES IN THE TIME OF THE COVID-19 PANDEMIC - Westi Bilda; Ahmad Fadillah; Dian Nopitasari (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The main purpose of this research is to produce android-based learning media products. The research carried out is development research with 4D models (define, design, dvelopment, dessimination). The sample in this study was a student of class X SMK Avicena Rajeg Tangerang Regency in 2021. The data in the study was collected using a questionnaire, which consists of an expert validation questionnaire, and a student response questionnaire as a user. Based on the results of the analysis of research data conducted obtained a value of 75.50% for media experts and 75.60% for material experts with good categories. The next stage is a practicality test and questionnaire on a small scale and obtained a score of 75.17% with good and practical categories. So it was concluded that android-based learning media is feasible and practically used in mathematical learning.